Gene expression analyses of GH/IGF axis in triploid crucian carp with growth heterosis - Qing, Weiling; Ren, Bingxin; Lou, Chenyi; Zhong, Huan; Zhou, Yi; Liu, Shaojun (Frontiers in Endocrinology, 2024)
Hybridization and polyploid breeding are the main approaches used to obtain new aquaculture varieties. Allotriploid crucian carp (3n) with rapid growth performance was generated by mating red crucian carp (RCC) with allotetraploids (4n). Fish growth is controlled by the growth hormone (GH)/insulin-like growth factor (IGF) axis. In the present study, we examined the expression characteristics of GH/IGF axis genes in hybrids F1, 4n, 3n, RCC and common carp (CC). The results showed that GHRa, GHRb, IGF1, IGF2, and IGF-1Ra were highly expressed in 3n compared with RCC and CC, whereas IGF3 was undetectable in the liver in RCC, CC and 3n. GHRa and GHRb had low expression in the 4n group. In hybrid F1, GHRa expression was low, whereas GHRb was highly expressed compared to the levels in RCC and CC. Moreover, in hybrid F1, the expression of IGF3 was higher, and the expression of IGF1 and IGF2 was lower than that in the RCC and CC, whereas the expression of IGF-1Ra was similar to that in RCC and CC. For the IGFBP genes, IGFBP1 had higher expression in 3n compared than that in RCC and CC, while other IGFBP genes were not high expressed in 3n. Among the genes detected in this study, 11 genes were nonadditively expressed in 3n, with 5 genes in the transgressive upregulation model. We proposed that the 11 nonadditive expression of GH/IGF axis genes is related to growth heterosis in 3n. This evidence provides new insights into hybridization and polyploid breeding from the perspective of hormone regulation.